Advances in A-to-I RNA editing in cancer - Yi Zhang; Lvyuan Li; Juana Jessica Mendoza; Dan Wang; Qijia Yan; Lei Shi; Zhaojian Gong; Zhaoyang Zeng; Pan Chen; Wei Xiong (Molecular Cancer)
Abstract RNA modifications are widespread throughout the mammalian transcriptome and play pivotal roles in regulating various cellular processes. These modifications are strongly linked to the development of many cancers. One of the most prevalent forms of RNA modifications in humans is adenosine-to-inosine (A-to-I) editing, catalyzed by the enzyme adenosine deaminase acting on RNA (ADAR) in double-stranded RNA (dsRNA). With advancements in RNA sequencing technologies, the role of A-to-I modification in cancer has garnered increasing attention. Research indicates that the levels and specific sites of A-to-I editing are significantly altered in many malignant tumors, correlating closely with tumor progression. This editing occurs in both coding and noncoding regions of RNA, influencing signaling pathways involved in cancer development. These modifications can either promote or suppress cancer progression through several mechanisms, including inducing non-synonymous amino acid mutations, altering the immunogenicity of dsRNAs, modulating mRNA interactions with microRNAs (miRNAs), and affecting the splicing of circular RNAs (circRNAs) as well as the function of long non-coding RNAs (lncRNAs). A comprehensive understanding of A-to-I RNA editing is crucial for advancing the diagnosis, treatment, and prognosis of human cancers. This review explores the regulatory mechanisms of A-to-I editing in cancers and examines their potential clinical applications. It also summarizes current research, identifies future directions, and highlights potential therapeutic implications.